2020
DOI: 10.3389/fimmu.2020.595039
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Nanovaccine Offers Protection Against Repeat Exposures to Trypanosoma cruzi Through Activation of Polyfunctional T Cell Response

Abstract: A parasitic protozoan Trypanosoma cruzi (T. cruzi) is the etiologic agent of Chagas disease. Previously, we have identified T. cruzi antigens TcG2 and TcG4 as potential vaccine candidates, cloned in eukaryotic expression vector pCDNA3.1 (referred as p2/4) and tested their ability to elicit protection from T. cruzi infection. In the present study, we subcloned the two antigens in a nanoplasmid that is optimized for delivery, antigen expression, and regulatory compliance standards, and evaluated the nanovaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…This showed that the effector and memory immune responses were fully effective. Although we are aware that an additional group of infected unvaccinated mice would have been the most suitable control group, none of the infected unvaccinated mice survived beyond 35 d.p.i.. Data reported by other groups using less virulent strains demonstrated that while some immunization protocols protected mice from rechallenge, the solely infection with T. cruzi did not [53][54][55][56] . The effectiveness of our immunization protocol to protect from rechallenges is highly relevant because, in the context of natural human infections, re-infections are frequent and are associated with risks of chronic manifestations of the disease 57,58 .…”
Section: Discussionmentioning
confidence: 88%
“…This showed that the effector and memory immune responses were fully effective. Although we are aware that an additional group of infected unvaccinated mice would have been the most suitable control group, none of the infected unvaccinated mice survived beyond 35 d.p.i.. Data reported by other groups using less virulent strains demonstrated that while some immunization protocols protected mice from rechallenge, the solely infection with T. cruzi did not [53][54][55][56] . The effectiveness of our immunization protocol to protect from rechallenges is highly relevant because, in the context of natural human infections, re-infections are frequent and are associated with risks of chronic manifestations of the disease 57,58 .…”
Section: Discussionmentioning
confidence: 88%
“… 71 This vaccine has produced positive phase 1 safety, tolerance, and immunological data (Covigenix VAX-001; NCT04591184). Preclinical studies of Nanoplasmid DNA vaccine vectors for Influenza, 72 Venezuelan equine encephalitis virus (VEEV), and Ebola virus, 73 and a DNA-based vaccine protecting against parasitic antigens expressed by T. cruzi 74 all demonstrated improved immune responses compared with plasmids. For example, VEEV Nanoplasmid vectors increased antibody response and significantly increased protection against VEEV challenge compared with a previously optimized pWRG7077-based plasmid comparator.…”
Section: Small Backbone Benefit: Reduced Vector Inactivation and Impr...mentioning
confidence: 99%
“… 73 In addition, Nanoplasmid delivered T. cruzi Chagas disease TcG2 and TcG4 antigens more efficiently protected infected mice than a pCDNA3.1 plasmid comparator. 74 …”
Section: Small Backbone Benefit: Reduced Vector Inactivation and Impr...mentioning
confidence: 99%
“…Integration of immune stimulants, like adjuvants, into nanovaccines augments the resulting immunogenicity. By fusing immune boosters, such as adjuvants, into nanovaccines, the resulting immunogenicity is magnified, amplifying immune responses and elevating vaccine effectiveness. …”
Section: Nanotechnology: a New Horizon For The Treatment And Diagnosismentioning
confidence: 99%